Impaired integrin α5/β1-mediated hepatocyte growth factor release by stellate cells of the aged liver - Rohn, Friederike; Kordes, Claus; Buschmann, Tobias; Reichert, Doreen; Wammers, Marianne; Poschmann, Gereon; Stühler, Kai; Benk, Amelie Saskia; Geiger, Fania; Spatz, Joachim P.; Häussinger, Dieter (Aging cell, 2020)
Hepatic blood flow and sinusoidal endothelial fenestration decrease during aging. Consequently, fluid mechanical forces are reduced in the space of Disse where hepatic stellate cells (HSC) have their niche. We provide evidence that integrin α5/β1 is an important mechanosensor in HSC involved in shear stress-induced release of hepatocyte growth factor (HGF), an essential inductor of liver regeneration which is impaired during aging. The expression of the integrin subunits α5 and β1 decreases in liver and HSC from aged rats. CRISPR/Cas9-mediated integrin α5 and β1 knockouts in isolated HSC lead to lowered HGF release and impaired cellular adhesion. Fluid mechanical forces increase integrin α5 and laminin gene expression whereas integrin β1 remains unaffected. In the aged liver, laminin β2 and γ1 protein chains as components of laminin-521 are lowered. The integrin α5 knockout in HSC reduces laminin expression via mechanosensory mechanisms. Culture of HSC on nanostructured surfaces functionalized with laminin-521 enhances Hgf expression in HSC, demonstrating that these ECM proteins are critically involved in HSC function. During aging, HSC acquire a senescence-associated secretory phenotype and lower their growth factor expression essential for tissue repair. Our findings suggest that impaired mechanosensing via integrin α5/β1 in HSC contributes to age-related reduction of ECM and HGF release that could affect liver regeneration.